Pengembangan Sistem Informasi Manajemen dalam Pendidikan Kristen - Tahoma Fetriany Siburian (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
The development of information systems in educational management has become a very necessary need to improve the efficiency and effectiveness of educational institution management. This study explores the concept and implementation of information systems in educational management in Christian educational institutions. The main focus of this study is to understand how information systems can support administrative processes, academic systems, curriculum management, and interactions between educators and students. This study uses a qualitative approach with a literature study method in several Christian educational institutions. The results of the study indicate that the implementation of appropriate information systems can improve the quality of educational services, facilitate access to information, and improve overall organizational performance. However, challenges such as limited resources and resistance to change need to be overcome to achieve successful implementation. This study provides practical recommendations for Christian educational institutions to optimize the use of information systems in their educational management.